1995
DOI: 10.1007/bf00125305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2,3-butanedione 2-monoxime (BDM) on ventricular trabeculae from the avian heart

Abstract: 2,3-butanedione 2-monoxime (BDM, 3-30 mM) decreased twitch force of intact ventricular trabeculae isolated from 19-day embryonic chick hearts in a dose-dependent manner. The responses to BDM were rapid and reversible. In an attempt to determine the cellular basis for the inhibitory effect of BDM, experiments were carried out on skinned muscle fibres and isolated myocytes. In trabeculae skinned with Triton X-100, BDM depressed maximum calcium activated force (Fmax) with an IC50 of 14 mM. At 3 mM BDM, the propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Ca release [12] and has also been shown to release Ca from the s.r. of avian ventricular trabeculae [4]. This interpretation is consistent with work on permeabilized canine myocytes, which found that a decrease of s.r.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ca release [12] and has also been shown to release Ca from the s.r. of avian ventricular trabeculae [4]. This interpretation is consistent with work on permeabilized canine myocytes, which found that a decrease of s.r.…”
Section: Introductionsupporting
confidence: 75%
“…One mechanism by which this may occur is a depression of the sarcolemmal L-type Ca current [1,4,6]. It has also been suggested that BDM may interfere with sarcoplasmic reticulum (s.r.)…”
Section: Introductionmentioning
confidence: 97%
“…The contractile properties of single Triton-skinned muscle fibers dissected from the four groups of muscle strips described above were determined as described by Brotto and Nosek [19,20]. The muscle fibers to be skinned were taken from the three muscle strips that had not been exposed to caffeine.…”
Section: Triton-skinned Muscle Fibersmentioning
confidence: 99%
“…At this concentration, BDM is known to suppress active myosin-actin interactions (e.g., Brotto et al, 1995). By applying this drug to the solution, we could therefore investigate whether such interactions contribute to passive tension.…”
Section: Strain Limit Of Cardiac Myofibrilsmentioning
confidence: 99%